2014
DOI: 10.1016/j.jobcr.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of curcumin with intralesional steroid injections in Oral Submucous Fibrosis – A randomized, open-label interventional study

Abstract: Turmix is beneficial and effective in reducing burning sensation in early OSMF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 12 publications
(12 reference statements)
11
56
1
Order By: Relevance
“…Similar non significant improvement in tongue protrusion was observed in the study conducted by Monu yadav et al [6] on 40 OSMF patients. The authors stated that conventional method of intralesional steroids was better in improving tongue protrusion.…”
Section: World Journal Of Pharmaceutical Researchsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar non significant improvement in tongue protrusion was observed in the study conducted by Monu yadav et al [6] on 40 OSMF patients. The authors stated that conventional method of intralesional steroids was better in improving tongue protrusion.…”
Section: World Journal Of Pharmaceutical Researchsupporting
confidence: 85%
“…Therefore the present study was conducted to evaluate the efficacy of systemic and topical application of curcumin in treating OSMF patients and results were obtained. Improvement of burning sensation was noted by many other authors like Monu Yadav et al [6] in his study on 40 OSMF patients concluded that curcumin is beneficial and effective in reducing burning sensation in OSMF patients as compared to the intra-lesional injections of corticosteroids and hyaluronidase. Rai B et al [7] in his study on 25 patients also stated that curcumin administration both topical and systemic lead to significant improvement in clinical symptoms (burning sensation) along with reduction in serum and salivary malondialdehyde levels.…”
Section: Discussionmentioning
confidence: 72%
“…Yadav et al. have reported complete resolution of burning sensation only with a curcumin group compared with intralesional medications . Das et al.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the literature reveals only 10 research papers assessing the use of curcumin in OSMF patients . These include randomized control trials, observational studies and a pre‐post study design.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Oral administration of curcumin was associated with an increase in vitamins C and E levels and a decrease in MDA and 8-hydroxydeoxyguanosine (8-OHdG) contents in the serum and saliva of patients with precancerous lesions.…”
Section: Oral Potentially Malignant Disordersmentioning
confidence: 99%